2022
DOI: 10.1007/s00520-022-07293-y
|View full text |Cite
|
Sign up to set email alerts
|

Life with a stoma across five European countries—a cross-sectional study on long-term rectal cancer survivors

Abstract: Purpose Stoma-related problems are known to be important to patients and potentially affect everyday life. The prevalence of stoma-related problems in rectal cancer survivors remains undetermined. This study aimed to examine aspects of life with a long-term stoma, stoma management, and stoma-related problems and explore the impact of stoma-related problems on daily life. Methods In total, 2262 patients from 5 European countries completed a multidimensional survey. Stoma-related problems were assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…Another concern was needing to know where the nearest toilet is or the limited choice of clothes that they can wear because of the pouch. These aspects are closer to the personal rather than the social dimension—a finding that is consistent with other European studies—and were more prevalent among women 36 . However, it is important to note that these aspects improved the most from the second to the third follow‐up, which highlights the personalised work carried out by the nurses in providing education on the safety of the pouch seal—which is key to avoiding urinary leaks as well as irritation of the peristomal skin— and allowing patients to return progressively to their daily routine, as reported in other studies 35 .…”
Section: Discussionsupporting
confidence: 90%
“…Another concern was needing to know where the nearest toilet is or the limited choice of clothes that they can wear because of the pouch. These aspects are closer to the personal rather than the social dimension—a finding that is consistent with other European studies—and were more prevalent among women 36 . However, it is important to note that these aspects improved the most from the second to the third follow‐up, which highlights the personalised work carried out by the nurses in providing education on the safety of the pouch seal—which is key to avoiding urinary leaks as well as irritation of the peristomal skin— and allowing patients to return progressively to their daily routine, as reported in other studies 35 .…”
Section: Discussionsupporting
confidence: 90%
“…The impact of stoma on patients' quality of life was explored in many dimensions. The stoma-related physical problems, including irritated parastomal skin and unpleasant odor, noted in our study, were also reported by other researchers (19,27,28).…”
Section: Discusionsupporting
confidence: 89%
“…Cirocchi et al reported that there was no advantage of SEMS placement for malignant obstruction of left-sied colon in terms of complications and postoperative mortality 13 , but it can increase the primary anastomosis rate and reduce the stoma. This is critical because it can affect the quality of life of the patient and thus have an impact on the overall health of the patient 14 . There were no postoperative deaths in this study, which may be related to the small sample size.…”
Section: Discussionmentioning
confidence: 99%